Bimbingan Kelompok Berbantuan Al-Qur'an Untuk Membangun Motivasi Beribadah Sholat Pada Remaja - Alda, Alda; Kusnadi, Kusnadi; Jannati, Zhila (CV. ITTC INDONESIA, 2023)
This study aims to find out the description of the motivation to pray in RT.05 youth before implementing Al-Qur'an assisted group guidance, to find out the implementation of Al-Qur'an assisted group guidance to build motivation to pray in RT youth. 05, and find out the description of the motivation to pray for teenagers in RT.05 after the implementation of Al-Qur'an assisted group guidance. This study uses a qualitative descriptive research method. There were 10 subjects in this study, namely clients is NA, NS, AAR, MH, CW, SN, JA, AR, JR, DD. Data collection techniques used are observation, interviews, and documentation. While the data analysis technique used is data reduction, data presentation and drawing conclusions or verification. The results of this study prove that prior to the implementation of the group guidance process, it shows that the subject still rarely performs the five daily prayers and still does not apply sincerity to perform the prayer services and does not yet have a sense of responsibility as a servant of His. The implementation of this guidance is carried out in six meetings with four stages of guidance, namely the formation stage, the middle stage, the activity stage and the termination stage. An overview of the motivation to pray for adolescents in RT.05 after carrying out group guidance assisted by the Qur'an, which can be seen that the subject has started trying to change and perform prayers diligently and earnestly, research subjects who are increasingly willing to try to pray with confidence and study the religious sciences and learn about prayer.